2012
DOI: 10.1002/asia.201201009
|View full text |Cite
|
Sign up to set email alerts
|

Large Two‐Photon Absorption of Terpyridine‐Based Quadrupolar Derivatives: Towards their Applications in Optical Limiting and Biological Imaging

Abstract: Developing organic chromophores with large two-photon absorption (TPA) in both organic solvents and aqueous media is crucial owing to their applications in solid-state photonic devices and biological imaging. Herein, a series of novel terpyridine-based quadrupolar derivatives have been synthesized. The influences of electron-donating group, type of conjugated bridge, as well as solvent polarity on the molecular TPA properties have been investigated in detail. In contrast to the case in organic solvents, bis(th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…To characterize the 2D networks, we anticipated the use of techniques including X‐ray photoelectron spectroscopy (XPS), X‐ray diffraction (XRD), small angle X‐ray scattering (SAXS), Brunauer–Emmett–Teller (BET) surface area measurements, scanning electron microscopy (SEM) or TEM, as well as solid state spectroscopic, calorimetric, and electrochemical methods. As two‐photon absorption (TPA) has been observed for conjugated terpyridines including some of our building blocks, we also chose to investigate multiphoton absorption and multiphoton absorption‐assisted Förster Resonance energy transfer (FRET) in our polymers and networks …”
Section: Building Blocks For Zinc‐terpyridine‐coordinated 1d 2d Andmentioning
confidence: 99%
See 2 more Smart Citations
“…To characterize the 2D networks, we anticipated the use of techniques including X‐ray photoelectron spectroscopy (XPS), X‐ray diffraction (XRD), small angle X‐ray scattering (SAXS), Brunauer–Emmett–Teller (BET) surface area measurements, scanning electron microscopy (SEM) or TEM, as well as solid state spectroscopic, calorimetric, and electrochemical methods. As two‐photon absorption (TPA) has been observed for conjugated terpyridines including some of our building blocks, we also chose to investigate multiphoton absorption and multiphoton absorption‐assisted Förster Resonance energy transfer (FRET) in our polymers and networks …”
Section: Building Blocks For Zinc‐terpyridine‐coordinated 1d 2d Andmentioning
confidence: 99%
“…This motivated us to study the TPA properties of their self‐assembled networks, and the 1D self‐assembled polymers have also shown large TPA, which was solvent dependent . It has been shown that alkylcarbazole as the donor and bis(styryl)benzene as a conjugation bridge in terpyridine‐based compounds, which are the basis for the development of our 1D, 2D, and 3D supramolecular networks and 2D metallocycles, enhance TPA cross sections in both organic solvent and aqueous media . Based on their large TPA cross section, these molecules have been tested for optical limiting materials.…”
Section: Nonlinear Optical Properties Of Terpyridine Ligands and Theimentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, these strategies are usually only valid in organic solvents . They suffer from poor photostability and serious fluorescence quenching in aqueous media or solid state due to aggregation to different extents, which is especially unfavourable for the applications in biological imaging and solid state devices . Therefore, developing organic chromophores with strong two‐photon excited fluorescence and high photostability in the solid state remains challenging for various practical applications …”
Section: Introductionmentioning
confidence: 99%
“…Multiphoton absorption (MPA) is of great theoretical and practical interests in a range of scientific and technical fields including photodynamic therapy, frequency upconverted lasing/stimulated emission, optical limiting (OL) and bioimaging etc [1][2][3][4][5][6][7][8][9]. Moreover, different requirements are needed to satisfy diverse application scenarios.…”
Section: Introductionmentioning
confidence: 99%